A structural study of the growth of ZnOx thin films by thermal evaporation in vacuum followed by heat treatment in air - Bulut, D.; Yukselici, M. H. (IOP PUBLISHING LTD, 2019)
ZnO thin films were grown on glass slides by thermal evaporation of zinc powder in vacuum followed by heat treatment in air. The films were characterized by x-ray diffraction (xrd), Raman scattering and scanning electron microscopy (SEM). Xrd pattern for as-deposited thin film sample consists of hexagonal Zn structure with slight wurtzite ZnO texture. It is observed that the heat-treatment at between 450 and 600 degrees C for 1 to 3 h turns the xrd pattern almost completely to wurtzite ZnO structure. SEM micrographs display flakes like hexagonal button shaped grains for as-deposited thin film which turns to needle like nanometer size structures with heat treatment. The red shift of some vibrational modes in Raman spectra for as-deposited thin film relative to the heat treated films and the introduction of a line at around 582 cm(-1) indicate that ZnO thin films have defects such as oxygen vacancies or zinc interstitials. The most intense Raman mode due to high frequency oxygen vibration for as-deposited zinc film is red-shifted by about 7 cm(-1) relative to the Raman mode for the ZnO thin film heat-treated.
Keywords: thin films; ZnO; physical vapor deposition; RAMAN-SCATTERING; OXIDE; SIZE; Materials Science